Medical outcasts: voices of undocumented Zimbabwean and Mexican women fighting gendered and institutionalized xenophobia in American and South African emergency health care - Richter, Roxane (My University, 2016)
This thesis is the culmination of medical aid work and 24 one-on-one interviews with undocumented Mexican women in the U.S.A. and Zimbabwean women in South Africa seeking lifesaving emergency healthcare access. The theoretical research combined with practitioner-based fieldwork, shows the direct and deplorable effects of xenophobic policies coupled with a demonstrable failure to enforce healthcare access rights.
A Thesis Submitted to the School of Social Sciences, in the Faculty of Humanities, in Fulfilment of the Requirement for the Degree of Doctor of Philosophy in Political Studies THE UNIVERSITY OF THE WITWATERSRAND JOHANNESBURG, SOUTH AFRICA NOVEMBER 2014
Keywords: Xenophobia--South Africa; Xenophobia--United States; Emergency medical services--South Africa; Emergency medical services--United States; Women immigrants--South Africa; Women immigrants--United States; Ethnicity; Zimbabweans--South Africa; Mexicans--United States; Gender identity